Implementasi Pembelajaran Mendalam: Berkesadaran (Mindful), Bermakna (Meaningful), dan Menggembirakan (Joyful) - Chotimah, Siti Chusnul; Suhartono, Suhartono; Fantofik, Didy (Prodi Pendidikan Keagamaan Islam, 2025)
This study aims to describe the implementation of deep learning at SMPIP Al Madinah as an effort to realize a meaningful, active, and student-centered learning process. The method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation of teachers and students. The results of the study show that the application of deep learning at SMPIP Al Madinah has included three main principles, namely mindful, meaningful, and joyful. Teachers act as facilitators who guide students to understand concepts in depth through project-based activities, reflection, and contextual discussions. This implementation has a positive impact on increasing learning motivation, critical thinking skills, and student independence. However, several obstacles were found, such as limited learning time and uneven understanding of the concept of deep learning. Overall, in-depth learning at SMPIP Al Madinah contributes to shaping the profile of Pancasila students who think critically, creatively, adaptively to the challenges of the 21st century.